Varieties of public-private policy coordination: how the political economy affects multi-actor implementation - Trein, Philipp; Tosun, Jale (Public policy and administration, 2021)
This study seeks to introduce the concept of Varieties of Capitalism to the study of multi-actor implementation arrangements. It illustrates the analytical value of this classification scheme by drawing from original empirical data and addresses two key research questions, namely how do public and private actors cooperate in delivering on public policy, and which factors determine the scope of their cooperation? To address these questions, the article examines governance arrangements adopted by individual European Union member states for implementing the Youth Guarantee. The Youth Guarantee was selected because all European Union member states must and have indeed already started to implement it, meaning it provides a broad empirical base for observing different types of public-private coordination. The findings demonstrate that a hierarchical structure in a country’s political economy and prior expenditure on active labour market policies result in different governance arrangements.
Gesehen am 15.08.2023